2018
DOI: 10.4236/ajps.2018.97105
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Potentiality of Silicon in Mitigation of Biotic and Abiotic Stresses in Plants: A Review

Abstract: The "quasi-essential element" silicon (Si) is not considered indispensable for plant growth and its accumulation varies between species largely due to differential uptake phenomena. Silicon uptake and distribution is a complex process involving the participation of three transporters (Lsi1, Lsi2 and Lsi6) and is beneficial during recovery from multiple stresses. This review focuses on the pivotal role of silicon in counteracting several biotic and abiotic stresses including nutrient imbalances, physical stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…Silicon application is an eco-friendly strategy to improve plants’ salinity stress response [ 19 ]. It boosts plant resistance to salinity and drought stress [ 20 , 21 ], reduces the negative impact of salt stress on chlorophyll content and biomass production [ 22 ], boosts adaptive responses, such as phenolic compound production, mineral uptake, and antioxidant activity [ 23 , 24 ]. Seed priming with sodium silicate enhanced germination characteristics and seedling vigor of wheat plants under drought stress [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silicon application is an eco-friendly strategy to improve plants’ salinity stress response [ 19 ]. It boosts plant resistance to salinity and drought stress [ 20 , 21 ], reduces the negative impact of salt stress on chlorophyll content and biomass production [ 22 ], boosts adaptive responses, such as phenolic compound production, mineral uptake, and antioxidant activity [ 23 , 24 ]. Seed priming with sodium silicate enhanced germination characteristics and seedling vigor of wheat plants under drought stress [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that Si increases plant resistance against biotic and biotic stresses (Epstein, 1999; Ma and Takahashi, 2002; Ma and Yamaji, 2006), such as salt and drought (Zhu and Gong, 2014; Rizwan et al, 2015), extreme temperature stress (Ma, 2004), nutrient deficiency (Marafon and Endres, 2013), aluminum toxicity (Galvez and Clark, 1991; Shen et al, 2014; Pontigo et al, 2015; Pontigo et al, 2017), disease resistance (Van Bockhaven et al, 2012; Marafon and Endres, 2013), and resistance to damage by wild rabbits (Cotterill et al, 2007). It also contributes to plant growth in different ways by enhancing multiple adaptive responses, such as antioxidant activity, mineral uptake, organic acid anion and phenolic compound exudation, the photosynthesis rate, the accumulation of compatible solutes, water status, and hormonal regulation (Barcelo et al, 1993; Cocker et al, 1998; Kidd et al, 2001; Al-Aghabary et al, 2005; Shahnaz et al, 2011; Shen et al, 2014; Sivanesan and Jeong, 2014; Kim et al, 2016; Kim et al, 2017; Tripathi et al, 2017; Ahanger et al, 2018; Ahmad et al, 2019a) and significantly reducing the adverse effects of salinity on chlorophyll levels and plant biomass (Seal et al, 2018). Despite this, most of these findings are scattered and need to come up with a comprehensive image of progress made on this topic.…”
Section: Introductionmentioning
confidence: 99%
“…S4). In other findings, it was reported that SiNPs might be owed to its role in increasing RNA polymerase expression and the activity of ribosomal proteins, which promote stress tolerance and reduce transpiration rate and oxidative stress, stabilizing the photosynthetic rate and eventually enhance fruit production 66 68 .…”
Section: Resultsmentioning
confidence: 98%